AKSESIBILITAS LAYANAN FISIK BAGI PENYANDANG DISABILITAS DI PERPUSTAKAAN UMUM DAERAH KABUPATEN JEMBER - Sari Dewi Poerwanti; Yudi Harianto Cipta Utama (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The Government of Jember Regency is actively implementing the Regional Regulation (PERDA) of Jember Regency No. 7 of 2016 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities, especially on equal distribution of access to information in public spaces, one of which is the library. This study discusses the accessibility of disabled users at the Regional Public Library of Jember Regency. The method used in this study is a qualitative description through data collection, interviews, observations and literature. The analysis of physical accessibility which includes parking areas, pedestrian paths, guide paths for library door services, circulation desks, signs, ramps, layouts and toilets so far has carried the spirit of a disability-friendly library, although it is not fully compliant with IFLA standards, but this is a capital for its development. management of the main causes of the program and the diversity of types of services with consideration of the degree of disability in the Jember Regency Public Library.